The Norton anthology of English literature audio companion - Abrams, M. H., (Meyer Howard), 1912-; Greenblatt, Stephen, 1943- (New York : Norton, 2001)
Features two CDs that provide readings and performances of selected poems from the seventh edition of "The Norton Anthology English Literature," including works read by the authors, passages of Old English and Middle English poems, and poems in Scots dialect, in sprung rhythm, and set to music.
Adult
Compact disc.
Keywords: English literature; Great Britain -- Literary collections